Faktor Penyebab Kehilangan Batubara Di Pit 15 PT Multi Harapan Utama Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Siti Asmasari; Agus Winarno; Tommy Trides; Windhu Nugroho; Shalaho Dina Devy (Retii, 2023)
The research was conducted in pit 15 of PT Multi Harapan Utama. In the process of mining activities in pit 15 in May 2023 in seam 14, 14X, 14XL, 15U, 15U1, and 15U2. There are several activities that result in coal losses, the amount of coal loss is 685 tons so the mining recovery is 98.74%. Coal loss in pit 15 occurred due to incomplete coal mining, coal re-cleaning, scattered coal not directly transported to the stockpile, waterlogged loading points, coal weighing, and distance of coal survey data collection.